Penyuluhan Pentingnya Konsumsi Tablet Tambah Darah pada Remaja Putri - Ramadhan, Muhammad Nur; Alwi, M Rusydi; Humaerah, Arifah; As Sholeha, Siti Khoirunnisa; ., Lathifatunnisa (Faculty of Engineering UNHAS, 2025)
The 112th Thematic Community Service Program (KKN) of Hasanuddin University in Mattiro Kanja Village, North Liukang Tupabbiring District, Pangkajene and Kepulauan Regency implemented a counseling program on the importance of iron supplement tablets (TTD) in preventing anemia. The problem that is often experienced by young women in the KKN location is anemia, which can cause stunting. The low level of awareness of young women about the importance of consuming iron supplement tablets and the lack of knowledge about the impact of anemia on health. Although they have been given iron supplement tablets since they were teenagers, many are still reluctant to consume them. The counseling activity was carried out for two days using the lecture method supported by attractive leaflet media, which was continued with the distribution of iron supplement tablets. Participants in this activity were 84 female students aged 10-18 years from various schools in the village. The counseling was divided into two sessions, namely the junior high school student session and the high school student session. Participants' knowledge was measured through pre-tests and post-tests, and the results were analyzed using SPSS ver. 27. This activity was successfully implemented where all participants, after the counseling, received and drank iron supplement tablets, which were directly supervised by Puskesmas officers. The results of the pre-test and post-test after the counseling was carried out showed an increase in students' knowledge of 33.3% of the counseling material provided. We expect this program to positively impact young women's compliance in consuming TTD and preventing anemia.